How demographic change will hit debt sustainability in European Union countries - Zsolt M. Darvas; Lennard Welslau; Jeromin Zettelmeyer (Bruegel, 2024)
Population ageing is putting pressure on the public debt-to-GDP ratios of European Union countries, both by raising net public expenditures and by lowering potential growth. To keep debt ratios under control and to comply with EU fiscal rules, EU countries will need to run sufficiently high structural primary balances - the difference between non-cyclical revenue and non-interest spending. Because the EU's fiscal rules require countries to anticipate and offset the fiscal costs of ageing during the adjustment period and in the 10 years beyond, the impact of ageing on overall fiscal indicators, such as the structural primary balance, will be felt mostly during the initial four-to-seven-year adjustment period that begins in 2025. Thereafter, structural primary balances will not need to rise further in most countries. However, in countries in which fiscal ageing costs are rising - all EU countries except Bulgaria, Croatia, Finland, France, Italy, Latvia and Sweden - fiscal adjustment in the non-ageing portion of the budget needs to continue, even if the structural primary balance does not need to increase. Unless ageing cost can be brought under control, this would require the re-allocation of expenditure from non-ageing to ageing-related items, or further increases in taxation. This creates difficult adjustment choices for many EU countries. Demographic risk factors could add one percentage point of GDP or more to required primary balances, while policies that alleviate demographic pressures - increasing immigration, raising fertility levels and labour force participation, boosting productivity and reducing the cost of long-term care for the elderly - could reduce fiscal pressures by around half a point. The annual country-specific recommendations (CSRs) issued as part of the European Semester include many good ideas to raise labour force participation, reform pension and healthcare systems and raise productivity, but implementation of these recommendations by EU countries has been limited. Furthermore, CSRs contain almost no advice on immigration policy or fertility-enhancing policies, despite a rich academic literature on both. EU countries need to act on existing CSRs to alleviate demographic pressures, while the Commission and the Council should go further in their advice on tackling demographic challenges.
Keywords: 330; financial regulation